Behavioral Analysis on IPv4 Malware in both IPv4 and IPv6 Network Environment - Muslim, Z.; Abdollah, M. F.; Osman, M. F. I.; Abu, N. A.; Sahib, S. (2011)
Malware is become an epidemic in computer net-work nowadays. Malware attacks are a significant threat tonetworks. A conducted survey shows malware attacks mayresult a huge financial impact. This scenario has becomeworse when users are migrating to a new environment whichis Internet Protocol Version 6. In this paper, a real Nimdaworm was released on to further understand the worm beha-vior in real network traffic. A controlled environment of bothIPv4 and IPv6 network were deployed as a testbed for thisstudy. The result between these two scenarios will be analyzedand discussed further in term of the worm behavior. The ex-periment result shows that even IPv4 malware still can infectthe IPv6 network environment without any modification. Newdetection techniques need to be proposed to remedy this problem swiftly.